Financial Self-Sufficiency of Ukrainian Territorial Communities: Evidence from Transcarpathian Communities Bordering Hungary - Bacho, Robert; Pataki, Gabor; Perchi, Oxana (Здобутки економіки: перспективи та інновації, 2026)
The article examines the financial self-sufficiency of territorial communities in Ukraine under budgetary decentralization, martial law and growing interregional asymmetry. The study focuses on the capacity of communities to generate own revenues, finance delegated and own powers, reduce dependence on transfers and maintain public services. The research combines theoretical generalization of international and Ukrainian approaches to fiscal autonomy with an empirical assessment of community budgets for 2021–2025. Special attention is paid to Transcarpathia and to communities bordering Hungary, where demographic, logistical, cross-border and wartime factors shape local fiscal capacity. The methodology includes indicator analysis, comparative regional assessment, clustering elements, an integrated financial self-sufficiency index and the adapted Brown test of municipal financial condition. The analysis uses indicators of per capita revenues and expenditures, administrative costs, capital expenditures, transfer dependency, the share of local taxes and fees, wage burden and spending on culture, physical education and sports. The results show that Ukrainian communities remain highly differentiated in terms of fiscal capacity. While some urban and economically diversified communities demonstrate high or optimal self-sufficiency, many peripheral, rural and small communities remain in low or critical categories. In Transcarpathia, Chop and Berehove show stable positions, while Batyovo demonstrates improvement; however, several Hungarian-border communities continue to face weak tax potential, high transfer dependence and limited investment capacity. The study concludes that financial self-sufficiency should be understood not only as budgetary independence, but also as the ability to ensure resilience, development and equitable access to services. Strengthening local tax bases, improving budget management and introducing targeted support mechanisms for vulnerable communities are essential for post-war recovery and sustainable development.